EDUCATIONAL EXPERIENCES: THE IMPORTANCE OF ROUTINE FROM THE PERSPECTIVE OF LITERACY - Amanda Wiebusch de Amorim, Thays; Biavati da Silva, Leidiany (Revista Gênero e Interdisciplinaridade, 2023)
The work entitled THE IMPORTANCE OF ROUTINE UNDER THE PERSPECTIVE OF LITERACY in the first stages of basic education: early childhood education and early years of elementary school I. E is a research based on the postulates of the sociointeractionist educator Vygotsky, in the National Curriculum Reference for Early Childhood Education (RCNEI) and the National Common Curricular Base (BNCC). The methodology is centered on a bibliographic research with a field trip and which refers to participant observation. The objective is to show such importance of the routine for literacy, this teaching methodology reaches the cognitive, affective and social dimensions that are important for the child to learn.